Study of underwater sound propagation and attenuation characteristics at the Yangjiang offshore wind farma - Xinze Huo; Peizhen Zhang; Ziyi Feng (Ecological Informatics)
The rapid growth of offshore wind farms has become a global priority, with both new and total installed capacities increasing sharply. Consequently, underwater noise generated with these developments has garnered significant attention. This study investigated the signals produced by 5.5 MW wind turbines at the Yangjiang offshore wind farm, focusing on various distances and depths. Results showed that the primary energy of the underwater noise was concentrated below 1500 Hz. At the same distance, deeper waters had lower noise levels than shallower waters. The discrete spectrum near the wind farm has a dominant frequency of 44 Hz. The peak sound pressure levels reach 93.76 dB at a depth of 10 m and 81.55 dB at 20 m, measured 50 m from the turbine. Horizontally, the sound pressure level of the dominant frequency decreased consistently as the distance from the wind farm increased. The sound transmission loss within 1 km is less than 10 dB, reaching 16.39 dB at 4 km, with noise levels nearing ambient ocean noise. A segmented spectral wide-angle parabolic equation was used to simulate the spatial sound field of the underwater noise, considering seabed topography. The noise propagation and attenuation models were validated against the measured data. Understanding noise propagation and attenuation with distance is crucial for selecting suitable offshore wind farm locations. Mitigating the impact of elevated underwater noise on sound-dependent species is essential for their survival.